PENGARUH KOMUNIKASI, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN : (Studi Kasus Pada Toko Diah Tasikmadu Karanganyar) - Diah Ayu Setianingrum; Santosa Tri Prabawa; Agus Triatmono (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of communication, product quality, and promotion on customer satisfaction at the Diah grocery store in Tasikmadu, Karanganyar. The study employs a quantitative approach using a survey method. The sample consists of 50 respondents who have made at least one purchase at the store. Data were collected via questionnaires and analyzed using multiple linear regression with the aid of IBM SPSS 25 software. The results indicate that, individually, neither communication nor product quality has a significant effect on customer satisfaction, whereas promotion does have a significant effect. However, when considered simultaneously, communication, product quality, and promotion all significantly influence customer satisfaction. Promotion is the most dominant variable influencing customer satisfaction.